Analisis Pengaruh Kinerja Keuangan Terhadap Keputusan Investasi Dengan Good Corporate Governance Sebagai Variabel Moderasi Pada Perusahaan Tekstil Dan Garmen Tahun 2019-2022 - Fitari, Defia Wanda; Kaharti, Eni (Politeknik Sawunggalih Aji, 2025)
This study seeks to examine the relationship between financial performance and investment choices in textile and garment industries from 2019 to 2022, with a focus on excellent corporate governance as a moderating component. Secondary data is being used in this quantitative study. The sample for this study consists of 21 firms from the textile and apparel sector that were listed on the Indonesia Stock Exchange between 2019 and 2022. The data used for this research comes from their financial reports and annual reports. A total of 21 samples were collected via the use of purposive sampling in the sample selection process, namely 9 companies with a four year period. The analytical tools used are descriptive analysis methods, quantitative analysis, as well as tests for classical assumptions, hypothesis testing, reliability, validity, and coefficient of determination (R2). Findings show that investment choices are heavily impacted by financial success, and that excellent corporate governance has little moderating effect on this connection